Effect of Cr on the evolution of microstructures in as-cast ternary niobium-silicide-based composites. (June 2017) - Maji, Poulami; Mitra, R.; Ray, K.K.
Abstract: The aim of this report is to present the effect of chromium on the detailed microstructural evolutions in Nb-Si-Cr ternary alloys. The microstructural characteristics of as-cast Nb-Si-Cr ternary alloys with five different compositions have been studied using SEM and XRD. In addition, the lattice parameter and the microhardness of the constituent phases were also estimated. The microstructures of the investigated alloys primarily reveal the presence of three phases: (Nb, Cr, Si)ss, Nb5 (Six, Cry )3 and Nb(Crx, Siy )2 . The nature, morphology and the amount of the phases, as well as that of the eutectic domains, are found to vary with the composition of the investigated alloys. The lattice parameter of the (Nb, Cr, Si)ss phase decreases, whereas that of the silicide phase first increases and then decreases with increasing concentration of Cr in the investigated alloys. The effect of Cr on the microhardness of (Nb, Cr, Si)ss is more significant compared to that of the adjacent silicide, or the laves phase or that of the eutectic domains. Highlights: Evolution of phases in Nb-Si-Cr alloys depends on the proportions of Nb, Si, and Cr. The observed microstructures follow the reported isotherms near Nb-rich region. Nb-Si-Cr alloys reveal lamellar or degenerated eutectic depending on the amount of Cr. Cr addition alters the Nbss lattice parameter and the silicide phase c/a ratio.